Pengaruh Strategi Pengelolaan Bahan Baku dan Efisiensi Biaya terhadap Kualitas Produk pada Mirah Catering - Yoni Mei Gantara; Muhammad Syihabuddin (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze the influence of raw material management strategies and cost efficiency on product quality at Mirah Catering in Surakarta. The research is motivated by the operational challenges commonly faced by catering businesses, particularly related to material availability, storage procedures, cost control, and consistency of food quality. A quantitative approach with an associative design was applied, involving a saturated sample of 56 employees directly engaged in production activities. Data were collected through structured questionnaires and analyzed using multiple linear regression supported by SPSS. The results indicate that raw material management strategies and cost efficiency show a positive direction of influence but are not statistically significant in improving product quality. The coefficient of determination (R² = 0.067) shows that both variables explain only 6.7% of variations in product quality, while the remaining 93.3% is influenced by other factors beyond the model. These findings imply that improvements in production standards, employee skills, and quality control procedures may play a more dominant role in determining product quality. The study contributes by integrating three operational variables—material management, cost efficiency, and product quality—into a single model within the catering industry context and provides practical recommendations for optimizing food production processes at small-to-medium catering businesses.